A Study in Scarlet - Doyle, Sir Arthur Conan (Italie ELI, 2016)
When Sherlock Holmes gets a letter from the police, he and his new friend, Doctor Watson, have a difficult problem. Who is the rich man in the empty house? Why did he die? And, most important of all, will Holmes and Watson find the man who did it? Or will they be too late?
Eli Readers is a beautifully-illustrated series of timeless classics and specially-Written stories for learners of English.
Contents, test.
Keywords: Crime; Reading books; Elementary level; Language Learning